Development of Teaching Materials for The Course Evaluation and Curriculum Development with Project-Based Learning for Students of S-1 Educational Technology at UNESA - Citra Fitri Kholidya; Bachtiar Syaiful Bachri; Lamidjan Hadi Susarno (BRILIANT: Jurnal Riset dan Konseptual, 2026)
This study aims to develop interactive teaching materials using a project-based learning approach and examine their effectiveness in enhancing students’ learning independence. The study employed a development research design combined with an experimental approach, following the ADDIE model (analysis, design, development, implementation, and evaluation). The participants consisted of 64 undergraduate students in the Educational Technology program at Surabaya State University, divided into an experimental group and a control group using a posttest-only control group design. The developed teaching materials were validated by one media expert and one material expert. The feasibility results indicated that the materials were highly feasible, with a score of 100% from the media expert and 87.17% from the material expert. To test effectiveness, students in the experimental group used the interactive teaching materials for independent learning, while the control group relied on conventional materials. Data were collected using questionnaires measuring students’ learning independence and analyzed using an independent samples t-test. The results showed that the experimental group achieved a higher mean score (M = 82.89) compared to the control group (M = 73.51). Statistical analysis revealed a significant difference between the two groups (p < .001), indicating that the developed teaching materials had a positive effect on students’ learning independence. These findings suggest that interactive teaching materials integrated with project-based learning can effectively support independent learning in higher education contexts and provide a practical solution to enhance student autonomy.